What endocrinologists can do to prevent cardiovascular complications in adults with Prader-Willi syndrome: Lessons from a case series - Pellikaan, Karlijn; van Weijen, Paula M. H.; Rosenberg, Anna G. W.; Hoekstra, Franciska M. E.; Vermaak, Michiel; Oomen, Peter H. N.; van der Lely, Aart J.; Cuypers, Judith A. A. E.; de Graaff, Laura C. G. (Frontiers in Endocrinology, 2023)
Context Prader-Willi syndrome (PWS) is a complex rare genetic syndrome. Mortality in patients with PWS is 3% per year. In nearly half of the patients, the cause of death is of cardiopulmonary origin. Prevention, diagnosis and treatment of cardiovascular (CV) disease in PWS adults is complicated by the behavioral phenotype, reduced ability to express physical complaints, high pain threshold and obesity. Objective To describe the challenges in prevention, diagnosis and treatment of CV disease in PWS adults, in order to increase awareness and improve medical care. Methods Retrospective study of medical records of adults visiting the Dutch PWS reference center. Results We describe the challenges encountered during diagnosis and treatment of four PWS adults with heart failure. All had pre-existent peripheral edema. CV risk factors in these patients were obesity (n=4), type 2 diabetes mellitus (n=2), hypertension (n=2), hypogonadism (n=3) and sleep apnea (n=2). Remarkably, all patients were younger than 40 years during their first cardiac decompensation. All patients presented with progressive shortness of breath and/or orthopnea and progressive pitting edema. In 117 controls with PWS without CV problems, 31% had leg edema. Conclusion Diagnosing CV problems in PWS adults is challenging. Peripheral edema is common in PWS adults without CV morbidity, which makes edema in general a poor marker for heart failure. However, when edema is of the pitting kind and progressive, this is a strong predictor of cardiac decompensation. We provide practical recommendations for diagnosing and treating CV problems in this vulnerable patient population.